2020
DOI: 10.3390/f11010083
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of European Mistletoe (Viscum album L.) on Forest Trees in Poland and Its Dynamics of Spread in the Period 2008–2018

Abstract: As recently reported, European mistletoe has become an important agent of damage to forest trees in Central Europe. To document the extent of its impact, host and environmental preferences, as well as spatial and temporal dynamics, we have analyzed the results of 10 years of annual assessments of tree damage in level 1 plots of country-wide national forest monitoring. Mistletoe was found on 12 forest tree species, most frequently on silver fir and Scots pine, much less often on birches and deciduous admixture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 36 publications
0
17
1
3
Order By: Relevance
“…According to available literature data, one of the most important factors determining the mistletoe distribution is temperature. It is believed that increasing average annual temperatures and climate change contribute to the mistletoe distribution in new areas [35]. However, in our study, an inverse correlation was found between temperature and mistletoe distribution parameters.…”
Section: Discussioncontrasting
confidence: 67%
“…According to available literature data, one of the most important factors determining the mistletoe distribution is temperature. It is believed that increasing average annual temperatures and climate change contribute to the mistletoe distribution in new areas [35]. However, in our study, an inverse correlation was found between temperature and mistletoe distribution parameters.…”
Section: Discussioncontrasting
confidence: 67%
“…This has led to the postponement of cuttings in the planned stands, and the further ageing of those stands. If older stands are more vulnerable [52], the current situation, in terms of age class, indicates that the forests are at increased risk of further destabilizing factors. The Romanian Technical Instructions set the amount of yield production (i.e., allowable cutting) at the level of growth.…”
Section: Discussionmentioning
confidence: 99%
“…Mistletoe ( Viscum album L.) is a hemiparasitic plant that develops stable haustoria in the host tree. According to studies conducted over the past few years, the intensity of mistletoe damage on trees in European countries increases from year to year [ 1 , 2 , 3 , 4 , 5 ]. Mistletoe infection causes damage to forests, gardens, plantations, and ornamental trees.…”
Section: Introductionmentioning
confidence: 99%
“…Mistletoe infection causes damage to forests, gardens, plantations, and ornamental trees. The affected host trees suffer from decreased growth and vigour, reduced fruiting, quality and quantity of wood, as well as weakened resistance to insect and fungal infestation [ 1 , 6 ]. Despite the fact that biological methods have recently been studied to slow down the spread of mistletoe, the only method of reducing the amount of mistletoe in urban and agricultural areas remains the mechanical removal of affected branches or the complete removal of trees [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%